Pengaruh Media Smart Ring Hoop Terhadap Kemampuan Motorik Kasar Anak Usia 4-5 Tahun Di Ra Nurul Huda Wanajaya - Awaliah, Nabilah Nur; Putri, Feronica Eka; Munafiah, Nida’ul (Peneliti.net, 2025)
This research aims to determine the effect of Smart Ring Hoop media on the gross motor skills of children aged 4-5 years in Ra Nurul Huda Wanajaya. Smart ring hoop media is learning media that has various sizes, from large, medium, to small. This smart ring hoop media is made from water hose, given several colors and equipped with other media such as balls, squares/squares, cones. This smart ring hoop media aims to improve children's gross motor skills such as stepping, jumping, catching, kicking, throwing, as a tool in carrying out the learning process. This research uses experimental quantitative research with a One Group Pretest-Posttest design. The subjects in this research were 20 children from group A Ar-Rahman at RA Nurul-Huda Wanajaya. Treatment was carried out in 8 meetings using smart ring hoop media. The results of this study prove that smart ring hoop media has an effect on the gross motor skills of children aged 4-5 years in Ra Nurul-Huda. This can be seen in the results of the Paired T test calculation between the pretest and posttest tcount results of 43.492 and ttable 1.729, which means that the tcount > ttable. So Ha is accepted and Ho is rejected, it can be concluded that there is a positive and significant influence of smart ring hoop media on the gross motor skills of children aged 4-5 years, so the use of this media can help children develop gross motor skills in children.